2018
DOI: 10.12688/wellcomeopenres.13423.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs of trachoma are prevalent among Solomon Islanders who have no persistent markers of prior infection with Chlamydia trachomatis

Abstract: The low population-prevalence of trachomatous trichiasis and high prevalence of trachomatous inflammation-follicular (TF) provide contradictory estimates of the magnitude of the public health threat from trachoma in the Solomon Islands. Improved characterisation of the biology of trachoma in the region may support policy makers as they decide what interventions are required. Here, age-specific profiles of anti-Pgp3 antibodies and conjunctival scarring were examined to determine whether there is evidence of ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Compared to previous population-based estimates of scar prevalence and severity, Tarawa is similar to areas with high ocular Ct infection prevalence, 33 and Vanuatu is similar to areas in Melanesia with low ocular Ct infection prevalence. 18 Ocular Ct infection was common in Tarawa, with almost 30% of the children aged 1-9 years having infection. The relationship between TF and ocular Ct infection in Tarawa resembles trachoma-endemic districts in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous population-based estimates of scar prevalence and severity, Tarawa is similar to areas with high ocular Ct infection prevalence, 33 and Vanuatu is similar to areas in Melanesia with low ocular Ct infection prevalence. 18 Ocular Ct infection was common in Tarawa, with almost 30% of the children aged 1-9 years having infection. The relationship between TF and ocular Ct infection in Tarawa resembles trachoma-endemic districts in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Data reviewed at the meeting from multiple EUs of the Solomon Islands, Vanuatu, and Papua New Guinea suggest that moderately high levels of TF in these populations are not reflective of ongoing intense ocular Ct transmission: the prevalence of ocular Ct infection is very low, and there is no increase in seropositivity among 1-to 9-year-olds. However, in the Solomon Islands, the absolute prevalence of antibody positivity in 1-to 9-year-olds is higher than that seen in other areas with low-intensity ocular Ct transmission [36]. The Solomon Islands have a high prevalence of urogenital Ct infection in women of reproductive age [37], which might explain this finding, potentially related to exposure of newborns to urogenital strains at the time of delivery, or exposure of children to ocular infection with urogenital strains through poor parental hand hygiene.…”
Section: Settings Where Indicators Divergementioning
confidence: 72%
“…The authors considered this to be much lower than may have been expected in an area where TF was common [ 14 ]. A recent study found no association between severe scarring, classed using the FPC grading system [ 64 , 65 ], and age [ 66 ]. Seroepidemiological analyses also provided little evidence of ongoing intense transmission of infection [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found no association between severe scarring, classed using the FPC grading system [ 64 , 65 ], and age [ 66 ]. Seroepidemiological analyses also provided little evidence of ongoing intense transmission of infection [ 66 , 67 ]. Other pathogens ( Adenoviridae , coagulase-negative Staphylococcus , Haemophilus influenza , Moraxella catarrhalis , Staphylococcus pneumonia and Staphylococcus aureus ) were sought in these samples using PCR, but none appeared to have significant association with TF.…”
Section: Resultsmentioning
confidence: 99%